al-Af‘āl al-Kalāmīyah al-Injāzīyah ‘inda Searle fī al-Qiṣṣah al-Qaṣīrah Lu’lu’at al-Ṣabāḥ li-Kāmil Kīlānī - Alya, Fihalisa Mughi Tri; Chotimah, Dien Nur (Al-Ma‘rifah, 2022)
This study aims to describe the various forms and functions of the illocutionary speech acts that contained in the Kāmil Kīlānī’s short story Lu’lu’at al-Ṣabāḥ. This research uses pragmatic approaches in descriptive qualitative studies. Using reading and taking notes as data collection techniques, and data reduction, data presentation techniques and making conclusion as data analysis techniques. The results of this study showed that there are five forms of speech act contained in conversations between the short story’s characters of Lu’lu’at al-Ṣabāḥ by Kāmil Kīlānī, namely assertive, directive, commissive, expressive, and declaration. The details are that there are 10 assertive speeches, 10 directive speeches, 2 commissive speeches, 1 expressive speech, and 1 declarative speech. And there are 11 functions of illocutionary speech act contained in the short story Lu’lu’at al-Ṣabāḥ by Kāmil Kīlānī: there are 2 speech functions of explaining, 3 speech functions of stating, 2 speech functions of telling, 3 speech functions of affirming, 4 speech function of advising, 4 speech function of requesting, 2 speech function of warning, 2 speech function of offering and threating, 2 speech function of sadness and setting.